2011
DOI: 10.1016/j.bcp.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Statin or fibrate chronic treatment modifies the proteomic profile of rat skeletal muscle

Abstract: Statins and fibrates can cause myopathy. To further understand the causes of the damage we performed a proteome analysis in fast-twitch skeletal muscle of rats chronically treated with different hypolipidemic drugs. The proteomic maps were obtained from extensor digitorum longus (EDL) muscles of rats treated for 2-months with 10mg/kg atorvastatin, 20mg/kg fluvastatin, 60mg/kg fenofibrate and control rats. The proteins differentially expressed were identified by mass spectrometry and further analysed by immunob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 65 publications
6
16
0
Order By: Relevance
“…Lovastatin supplementation had impaired the energy production system in the skeletal muscle, particularly in the metabolism of carbohydrate and creatine. Similar observations have been reported on the extensor digitorum longus muscle of rats treated for 2-months of 10mg atorvastatin/kg BW and 20mg fluvastatin/kg BW [29]. The impairment in the energy production system could play a major role in the development of muscle damage, which is consistent with the adverse effects observed on the longissimus thoracis et lumborum muscle through histological examination.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Lovastatin supplementation had impaired the energy production system in the skeletal muscle, particularly in the metabolism of carbohydrate and creatine. Similar observations have been reported on the extensor digitorum longus muscle of rats treated for 2-months of 10mg atorvastatin/kg BW and 20mg fluvastatin/kg BW [29]. The impairment in the energy production system could play a major role in the development of muscle damage, which is consistent with the adverse effects observed on the longissimus thoracis et lumborum muscle through histological examination.…”
Section: Discussionsupporting
confidence: 86%
“…Through this metabolic process, high energy adenosine triphosphate (ATP) molecules and reduced nicotinamide adenine dinucleotide (NADH) are generated. Similar observations of down-regulation of glycolytic enzymes in the skeletal muscle have also reported previously in rat and the down-regulation of glycolytic enzymes is a symptom of energy production failure, and can contribute to muscle damage [29]. In humans, hereditary muscle glycogenoses are characterized by defective glycolytic enzymes and leads to different degree of myopathy [30].…”
Section: Discussionsupporting
confidence: 71%
“…There are several case reports of induction of inflammatory myopathies (i.e., polymyositis and dermatomyositis) by statins, but many (25 cases of a histologically distinct statin myopathy) muscle biopsies demonstrated necrotising myopathy without significant inflammation. Other studies showed that atorvastatin (10 mg/kg for 2 months in rats) may induce a down-regulation of the expression of proteins essential for skeletal muscle function (Camerino et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms activated in statin-induced myopathy include the inhibition of mevalonic acid production, a precursor in the synthesis of ubiquinone (CoQ10) [12], the modification of the expression of proteins needed in cellular protection against oxidative stress [13], the changes in the mitochondrial respiratory chain with consecutive depolarization of the mitochondrial internal membrane, alteration of calcium homeostasis and appearance of "calcium waves" [14]. Since mitochondrial dysfunction might be induced by CoQ10 deficiency, a meta-analysis of randomized controlled trials analyzed the effects of CoQ10 supplementation in patients with statin-induced myopathy.…”
Section: Introductionmentioning
confidence: 99%